Entrenchment effects in code-mixing: Individual differences in German-English bilingual children - Quick, Antje Endesfelder; Backus, Ad; Lieven, Elena (Cognitive Linguistics, 2021)
Following a usage-based approach to language acquisition, lexically specific patterns are considered to be important building blocks for language productivity and feature heavily both in child-directed speech and in the early speech of children (Arnon, Inbal & Morten H. Christiansen. 2017. The role of multiword building blocks in explaining L1-L2 differences. Topics in Cognitive Science 9(3). 621-636; Tomasello, Michael. 2003. Constructing a language: A usage-based theory of language acquisition. Cambridge: Harvard University Press). In order to account for patterns, the traceback method has been widely applied in research on first language acquisition to test the hypothesis that children's utterances can be accounted for on the basis of a limited inventory of chunks and partially schematic units (Lieven, Elena, Dorothé Salomo & Michael Tomasello. 2009. Two-year-old children's production of multiword utterances: A usage-based analysis. Cognitive Linguistics 20(3). 481-508). In the current study, we applied the method to code-mixed utterances (n = 1,506) of three German-English bilingual children between 2 and 4 years of age to investigate individual differences in each child's own inventory of patterns in relation to their input settings. It was shown that units such as I see X as in I see a Kelle 'I see a trowel' could be traced back to the child's own previous productions. More importantly, we see that each child's inventory of constructions draws heavily on multiword chunks that are strongly dependent on the children's language input situations.
CRIS-Team Scopus Importer:2022-11-17
Keywords: bilingual first language acquisition; code-mixing; entrenchment; individual differences; usage-based